Frondoside A potentiates the effects of conventional therapeutic agents in acute leukemia. (December 2017) - Sajwani, F.H.; Collin, P.; Adrian, T.E.
Graphical abstract: Highlights: Frondoside A markedly inhibits the proliferation of acute leukemia blast cells. Acute T-lymphoblastic leukemia (CCRF-CEM) cells are very sensitive to Frondoside A. Monocytic (THP-1) and promyelocytic (HL-60) leukemia cells were less sensitive. Frondoside A acts synergistically with conventional anti-leukemic agents. Abstract: Acute leukemia is the major cause of mortality in hematological malignancies. Despite improvement of survival with current chemotherapies, patients die from the disease or side-effects of treatment. Thus, new therapeutic agents are needed. Frondoside A is a triterpenoid glycoside originally isolated from the sea cucumber, Cucumaria frondosa that has potent antitumor effects in various cancers. The current study investigated the effects of frondoside A in acute leukemia cell lines alone and in combination with drugs used for this malignancy. This study is the first comparing the efficacy of frondoside A to available conventional drugs. The acute leukemia cell lines used were CCRF-CEM, HL-60 and THP-1. Cells were cultured and treated with different concentrations of vincristine sulphate, asparaginase and prednisolone alone and in combination with frondoside A. The inhibitory concentration 50 (IC50 ) for each compound was determined for the cell lines. CCRF-CEM cells were very sensitive to frondoside A treatment while HL-60 and THP1 were less sensitive. Frondoside A markedly enhanced the anticancer effects of all of the conventional drugs. Synergistic effects were seen with most of the combinations. Frondoside A may be valuable in the treatment of acute leukemia, particularly when used in combination with current therapeutic drugs.